REAKSI PASAR TERHADAP KENAIKAN BIAYA BAHAN BAKAR DI SEKTOR YANG DIRESPON SEBAGAI KABAR BURUK DAN BAIK - Dwi Gita Noramalia; Lindrianasari Lindrianasari (ITB AAS Indonesia Surakarta, 2023)
In general, the increase in fuel prices is viewed as bad news for the industrial world. However, the fuel price increase supports palm oil and coal revenue. Therefore, it is necessary to study investors' reactions to the increase in fuel prices to determine whether it will affect the company's value. This study aims to provide empirical evidence regarding whether the announcement of an increase in fuel prices on September 3rd, 2022, caused a market reaction. To determine the reactions that occur, the indicators used in analyzing whether there is a reaction in this study are abnormal returns and trading volume activity. Furthermore, this study used the population of sectors that respond to fuel price increases as bad news and sectors that react to good news. The analysis technique used was the Compare Means test and the Mann-Whitney test. The study results show a negative market reaction in sectors that perceive fuel price increases as bad news, so it causes a decrease in abnormal returns. Meanwhile, positive market reactions occur in sectors that perceive fuel price increases as good news, as indicated by increased abnormal returns. In addition, the rise in fuel prices affects stock movements in the capital market which are proved by the presence of significant trading volume activity around the event period in all sectors studied so that it cause a market reaction.